Exploring the potential of Orthodillo Chiltoni in the bioremediation of cellulosic wastes: A study of isopoda efficiency and mechanisms - Salman, Zainab Hamed; Alsalman, Ibrahim Mahdi (International Journal of Innovative Research and Scientific Studies, 2025)
Terrestrial isopods are integral to the biodegradation of various waste materials, playing a significant role in nutrient cycling and delivering essential ecosystem services. This study evaluates the potential of Orthodillo chiltoni as a model organism for bioremediation in urban settings, with an emphasis on the degradation of municipal, agricultural, park, and market wastes. To assess the biodegradation efficacy of O. chiltoni, we conducted experiments using a range of waste materials—including potato peels, orange leaves, thyme plants, sawdust, and cardboard—under controlled laboratory conditions that simulated the natural habitat of the species. These conditions were optimized for temperature, humidity, and lighting to ensure the methodological rigor and accuracy of the data obtained. The results indicated that O. chiltoni exhibited significant efficiency in the consumption of the waste materials, with consumption rates quantified at 99.525% for potato peels, 87.15% for orange leaves, 78.225% for sawdust, 66.8% for thyme plants, and 61.6% for cardboard residues. The consumption efficiency per individual isopod was measured at 0.796 mg for potato peels, 0.697 mg for orange leaves, 0.625 mg for sawdust, 0.534 mg for thyme plants, and 0.492 mg for cardboard residues. These findings highlight the considerable bioremediation potential of O. chiltoni, indicating that other terrestrial isopod species may also be effective in the biological treatment of various waste types. Future investigations are warranted to examine the applicability of different isopod species across a range of waste treatment contexts, thereby advancing our knowledge and application of these organisms in environmental remediation strategies.